Listening Comprehension Performance and Problems: A Survey on Undergraduate Students Majoring in English - Hariswan Putera Jaya; Ismail Petrus; Dedi Kurniawan (Indonesian Research Journal in Education |IRJE|, 2021)
This study was aimed at finding out the performance of listening comprehension, problems faced, the causes of the problems, and the relationships between the problems and their causes. The samples of this study were the students of bachelor program of an English education study program. The data were the TOEFL prediction listening comprehension test and questionnaires. It was found that 30% of the samples were in a fair listening category and 70% were in a poor listening category. The students’ main problems in listening were then categorized as listeners, listening materials, and listening settings. The causes of the problems were specified as linguistic knowledge, pronunciation, concentration, and environment. The data were analyzed using chi-square association with p-value 514.84 which was greater than the critical value of 179.58. Therefore, there is a significant relationship between the listening problems and the factors causing the problem.